Analisis Penerapan Sanksi Terhadap Pegawai Negeri Sipil Terkait Dengan Penggelapan Barang Persediaan Milik Negara Berdasarkan Hukum Penyelenggaraan Negara (Studi Kasus di Rumah Tahanan Negara Klas I Bandung) - Indra Ganjar Nugraha (Jurnal Media Justitia Nusantara, 2018)
Essentially organizing the task of the Indonesian state government for the welfare of its people is carried out by providing services to the community. The services in question can be direct or indirect, carried out alone, or submitted to other parties. The administration of daily government is carried out by a [government paratur which is currently known as the State Civil Apparatus (ASN). In carrying out its duties and functions to provide services to the community, the State Civil Apparatus must submit and comply with the prevailing laws and ethics in carrying out their duties and functions. Based on this thought, the identification of the research problem was formulated as follows: (1) Are civil servants who have been subjected to sanctions for compensation and other administrative sanctions for the same mistakes can they be asked for criminal liability? and (2) How is the handling of the problem of inventory items internally related to the applicable regulations? The objectives of this study are: (1) to be able to find out whether civil servants who have been subject to sanctions for compensation and other administrative sanctions for the same mistakes can be asked for criminal liability, and (2) in order to illustrate how to handle the problem solving of goods supply internally related to the prevailing laws and regulations.This thesis research uses normative legal research methods or library research because this research places secondary data as primary legal material. Normative legal research is qualitative where the data used is not in the form of numbers, but is a description of words in a sentence.The results obtained from this thesis research are: (1) Civil Servants who have been subjected to sanctions for compensation and / or other administrative sanctions for the same mistakes can also be asked for criminal liability, and (2) handling the problem of supply items (procurement problems rice) that occurred in Bandung's Jail Class I was based on law, but not in accordance with all applicable laws and regulations.